Intracranial Hypotension as a Cause of Radiculopathy from Cervical Epidural Venous Engorgement: Case Report - Albayram, Sait; Wasserman, Bruce A.; Yousem, David M.; Wityk, Robert (American Journal of Neuroradiology, 2002)
Summary: We describe the case of a 40-year-old man with spontaneous intracranial hypotension who presented with cervical radiculopathy associated with epidural venous engorgement. Epidural venous engorgement can occur secondary to intracranial hypotension and manifests intracranially as pachymeningeal venous engorgement. In the cervical spine, two cases of epidural venous engorgement due to intracranial hypotension have been reported in the literature, and neither patient presented with symptoms related to nerve compression. Epidural venous engorgement should be considered in the differential diagnosis of an enhancing epidural mass in the cervical spine. Diagnostic clues include sparing of the anterior midline and posterior aspects of the epidural space and, if present, pulsation artifact.